A study of picture archiving and communication system adoption in one hospital: Applying the unified theory of acceptance and use of technology model - Jahanbakhsh, Maryam; Nazemi, Zahra; Mohammadi, Farakhlaghah; Hasanzadeh, Akbar (Journal of Education and Health Promotion, 2018)
CONTEXT: The advent of picture archiving and communication system (PACS) as medical image information system represent a major change of work pattern for radiologists and physicians and has proved to be a substantial challenge to the organization. AIMS: The study aimed to investigate the factors affecting the use of PACS through the unified theory of acceptance and use of technology model. SETTINGS AND DESIGN: It was an applied and analytical study. SUBJECTS AND METHODS: Ninety questionnaires were distributed in Kashani hospital of Esfahan which implemented web-based PACS, and 45 usable questionnaires were returned. The questionnaire consists of scales for performance expectancy (PE), effort expectancy, facility condition, social influences, and behavioral intention (BI) and was developed by the author comparing the similar studies in which validity was confirmed by a committee of experts and the reliability was calculated using a Cronbach's α (α = 0.946). STATISTICAL ANALYSIS USED: Data were analyzed using SPSS version 20. The statistical tests for data analysis were Pearson's correlation and multiple regression analysis. RESULTS: The findings suggested a direct correlation between BI and factors of PE (P < 0.001, r = 0.788), effort expectancy (P < 0.001, r = 0.564), social influences (P = 0.001, r = 0.472), and facility condition (P < 0.001, r = 0.477). CONCLUSIONS: According to the findings, only the PE is sufficient for predict and evaluation of user behavior toward PACS. The results could be useful in terms of designing new systems and understanding users' need.